Design for sustainability a sourcebook of integrated, eco-logical solutions - Birkeland, Janis, 1945- (Earthscan Publications, 2002)
Ecological principles and concepts are becoming increasingly integrated into our everyday lives, influencing where and how we live. This book is an inspiring, radical and detailed collection of the eco-solutions that can be applied to a range of design challenges.
Keywords: Ecological engineering.; Sustainable development.; elektronické knihy; electronic books